FIRST RECORD OF GYMNETIS STELLATA LATREILLE, 1833 (SCARABAEIDAE: CETONIINAE) FOR PERU - Juárez N., Gino (2015)
A new record for Peru is cited: Gymnetis stellata Latreille (Scarabaeidae: Cetoniinae), registered at the campus of Piura National University, an important area of dry forest of Piura Region, Peru.